Bamboonomic: Ekonomi Bambu Pendukung Desa Wisata Tegaren - Jojok Dwiridhotjahjono; Prihandono Wibowo; Praja Firdaus Nuryananda (Magister Tourism Study, Faculty of Tourism, Udayana University, 2020)
Tegaren village is the biggest besek producer in Trenggalek, East Java. In collaboration with UPN